Inhibition of early response genes prevents changes in global joint metabolomic profiles in mouse post-traumatic osteoarthritis. Issue 3 (March 2019) - Haudenschild, D.R.; Carlson, A.K.; Zignego, D.L.; Yik, J.H.N.; Hilmer, J.K.; June, R.K.
Summary: Objective: Although joint injury itself damages joint tissues, a substantial amount of secondary damage is mediated by the cellular responses to the injury. Cellular responses include the production and activation of proteases (MMPs, ADAMTSs, Cathepsins), and the production of inflammatory cytokines. The trajectory of cellular responses is driven by the transcriptional activation of early response genes, which requires Cdk9-dependent RNA Polymerase II phosphorylation. Our objective was to determine whether inhibition of cdk9-dependent early response gene activation affects changes in the joint metabolome. Design: To model post-traumatic osteoarthritis, we subjected mice to non-invasive Anterior Cruciate Ligament (ACL)-rupture joint injury. Following injury, mice were treated with flavopiridol – a potent and selective inhibitor of Cdk9 kinase activity – to inhibit Cdk9-dependent transcriptional activation, or vehicle control. Global joint metabolomics were analyzed 1 h after injury. Results: We found that injury induced metabolomic changes, including increases in Vitamin D3 metabolism, anandamide, and others. Inhibition of primary response gene activation immediately after injury largely prevented the global changes in the metabolomics profiles. Cluster analysis of joint metabolomes identified groups of injury-induced and drug-responsive metabolites. Conclusions: Metabolomic profiling provides an instantaneous snapshot of biochemical activity representing cellular responses. We identified two sets of metabolites that change acutely after joint injury: those that require transcription of primary response genes, and those that do not. These data demonstrate the potential for inhibition of early response genes to alter the trajectory of cell-mediated degenerative changes following joint injury, which may offer novel targets for cell-mediated secondary joint damage.